SEASONAL VARIATION IN THE PHYSICO-CHEMICAL PARAMETERS OF OWALLA RESERVOIR, OSUN STATE, NIGERIA - MUSTAPHA, A. K; OLALEYE, V. F. (Nigerian Journal of Fisheries, 2021)
Fishes are threatened due to unwanted changes in the physical, chemical and biological properties of water. The need for efficient monitoring of the Physico-chemical parameters in Owalla reservoir is becoming pertinent with reports of a decline in fish production due to unsustainable exploitation. The water quality of the reservoir was monitored to reveal the extent of its contamination, and suitability for fishes and other aquatic organisms. The Physico-chemical characteristics; temperature, pH, dissolved oxygen, alkalinity, total hardness, turbidity, and conductivity of water samples from selected points in the reservoir were analysed using standard methods for twenty-four (24) months. From the Data obtained the mean values for; temperaturewas25.16 ± 0.34 oC, pH 7.44 ± 0.26, dissolved oxygen 7.31 ± 0.36 mg/L, alkalinity 64.11 ± 0.46mg/L, total hardness 41.72 ± 0.78 mg/L, turbidity 34.95 ± 5.67 NTU and Conductivity 61.87 ±7.01µSc. The values obtained indicated that the reservoir is not under heavy stress as the mean values of the determined parameters were found to be within the permissible limits.